An essential role of adenosine deaminase acting on RNA 1 in coeliac disease mucosa - Di Fusco, Davide; Segreto, Maria Teresa; Iannucci, Andrea; Maresca, Claudia; Franzè, Eleonora; Di Maggio, Giulia; Di Grazia, Antonio; Boccanera, Siro; Laudisi, Federica; Marafini, Irene; Paoluzi, Omero Alessandro; Michienzi, Alessandro; et al. (Frontiers in Immunology, 2023)
Background and aim Type I interferons (IFNs) are highly expressed in the gut mucosa of celiac disease (CD) gut mucosa and stimulates immune response prompted by gluten ingestion, but the processes that maintain the production of these inflammatory molecules are not well understood. Adenosine deaminase acting on RNA 1 (ADAR1), an RNA-editing enzyme, plays a crucial role in inhibiting self or viral RNAs from activating auto-immune mediated responses, most notably within the type-I IFN production pathway. The aim of this study was to assess whether ADAR1 could contribute to the induction and/or progression of gut inflammation in patients with celiac disease. Material and methods ADAR1 expression was assessed by Real time PCR and Western blotting in duodenal biopsy taken from inactive and active celiac disease (CD) patients and normal controls (CTR). To analyze the role of ADAR1 in inflamed CD mucosa, lamina propria mononuclear cells (LPMC) were isolated from inactive CD and ADAR1 was silenced in with a specific antisense oligonucleotide (AS) and then incubated with a synthetic analogue of viral dsRNA (poly I:C). IFN-inducing pathways (IRF3, IRF7) in these cells were evaluated with Western blotting and inflammatory cytokines were evaluated with flow cytometry. Lastly, the role of ADAR1 was investigated in a mouse model of poly I:C-driven small intestine atrophy. Results Reduced ADAR1 expression was seen in duodenal biopsies compared to inactive CD and normal controls. Ex vivo organ cultures of duodenal mucosal biopsies, taken from inactive CD patients, stimulated with a peptic-tryptic digest of gliadin displayed a decreased expression of ADAR1. ADAR1 silencing in LPMC stimulated with a synthetic analogue of viral dsRNA strongly boosted the activation of IRF3 and IRF7 and the production of type-I IFN, TNF-α and IFN-γ. Administration of ADAR1 antisense but not sense oligonucleotide to mice with poly I:C-induced intestinal atrophy, significantly increased gut damage and inflammatory cytokines production. Conclusions These data show that ADAR1 is an important regulator of intestinal immune homeostasis and demonstrate that defective ADAR1 expression could provide to amplifying pathogenic responses in CD intestinal mucosa.